Potential Role of Probiotic Strain Lactiplantibacillus plantarum in Control of Histamine Metabolism - Gina Cavaliere; Egidia Costanzi; Beniamino Cenci-Goga; Marco Misuraca; Giovanna Traina (Biology)
Histamine intolerance is a condition that occurs when there is an imbalance between the accumulation and degradation of histamine within the body. Excess histamine is metabolized and then degraded by two enzymes, of which the most abundant is the vesicular diamine oxidase (DAO). An imbalance or a state of dysbiosis of the intestinal microbiota has been observed in patients with histamine intolerance compared to healthy individuals. Studies indicate that the administration of bifidobacteria or lactobacilli alone or in mixtures can alter colonic microbiota populations and metabolic activities. The present study has evaluated the ability of a probiotic bacterial strain to stimulate the release of cellular DAO from an in vitro model of the human intestinal epithelial barrier. The results indicate that, under the experimental conditions used, probiotic strain Lactiplantibacillus plantarum LP115 has a significant stimulatory effect on DAO secretion in adenocarcinoma cell line HT-29.